TEHNIK PENGUMPULAN DATA DALAM PENELITIAN PENDIDIKAN - Rumina, Rumina (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Data collection methods are techniques or methods used by researchers in collecting data. The technique of designating a word that is abstract and not manifested in objects, but its use can only be seen through: questionnaires, interviews, observations, exams (tests), documentation, etc. The first step for researchers in analyzing the data that has been collected is to review the research proposal in order to check the plan for presenting the data and implementing the analysis that was previously determined. Nowadays, research in the field of education and other behavioral sciences is often complex and requires calculation work, in order to achieve accuracy and to save time and energy. Data collection techniques are a very important step in the scientific method. Data collection methods are divided into two, namely direct observation methods and methods using questions, data collection techniques or methods consist of quantitative methods and qualitative methods, namely data collection by interview, questionnaire, observation and a combination of the three.